The impact of altered hands function on working ability of patients with systemic sclerosis - Vidaković, Predrag; Damjanov, Nemanja (Vojnosanitetski pregled, 2021)
Background/Aim. Hand impairment in systemic sclerosis (SSc) patients is the most frequent manifestation of this progressive disease and often cause problems in daily activities and working ability. The correlation of altered hand functions in patients with SSc and their impact on working ability is not fully explained. The objective of this study is to assess the impact of altered hand functions of patients with SSc on their working ability. Methods. We assessed 20 patients with SSc (17 females, 3 males), with mean age of 45.5 ± 11.9 years (min 29, max 69, Med 44.0 years). The movements of fingers, wrist and forearm were examined by measuring active range of motion of the hand and fingers, muscle strength of the fingers, the skin lesions by modified Rodnan score, the function of the fingers, hands and forearms by the Hand Mobility in Scleroderma (HAMIS) test, as well as the condition of the capillaries in the fingers by capillaroscopy and working capacity by Work Ability Index (WAI). Results. Reduced strength on at least one tested muscle, was established in all patients, thickening of the skin on the hands in 14/20 (70%) and the fingers in 19/20 (95%), “scleroderma type” capillary changes in 15/17 (85%), decreased range of motion in finger joints in 16/20 (80%) of the patients. Also, 14/20 (70%) of subjects reported problems at work [decrease performance achieved in 8/20 (40%), reduction of working hours in also 8/20 (40%), leaving out some of the work in 14/20 (70%), and investing of extra effort in 15/20 (75%)]. By means of WAI, work ability assessment questionnaire, it was found that the working capacity was reduced in 11/20 (55%) of our patients. None of the patients was in the group of the most serious cases, the “poor” category; in the “moderate” category there were 6/20 (30%), while 5/20 (25%) of the patients were in the group with minimally reduced working capacity (“good” category). There was a statistically significant correlation between the thickened skin on the fingers (p < 0.05), reduced muscle strength in the fingers (p < 0.002) and limited mobility of the individual finger joints (p < 0.05), with information on reduced working capacity obtained by means of WAI questionnaire and with answers to questions about problems at work. Conclusion. The thickened skin on the fingers, reduced fingers muscle strength and limited mobility of certain finger joints in patients with SSc cause decreasing working capacity for all jobs that include manual activities.
Keywords: scleroderma, systemic; work capacity evaluation; hand